THE RELATIONSHIP OF INTIMATE FRIENDSHIP WITH SELF DISCLOSURE TO PSYCHOLOGICAL WELL-BEING IN SECOND ACCOUNT INSTAGRAM USERS IN SIDOARJO - Wahyu Arfianti, Vindy; Hardi Ansyah, Eko (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the relationship between intimate friendship and self-disclosure on psychological well-being among users of Instagram second accounts, who often utilize these platforms as safe spaces for emotional expression. Method: Employing a quantitative correlational approach, the study investigates the influence of intimate friendship and self-disclosure using multiple linear regression analysis. Results: The findings reveal a significant positive relationship between intimate friendship and psychological well-being (r = 0.504; p < 0.001), as well as between self-disclosure and psychological well-being (r = 0.455; p < 0.001). Furthermore, both variables simultaneously contribute to psychological well-being with a combined influence of 46% (R² = 0.464), suggesting that the remaining variance is accounted for by other external factors. Novelty: This research provides new empirical insights into the underexplored area of psychological well-being in the context of social media, particularly focusing on Instagram second account users. It emphasizes the psychological value of close interpersonal relationships and open communication in enhancing well-being within digital platforms.